Business Ethics - A Philosophical and Behavioral Approach - Conrad, Christian A. (Springer International Publishing, 2018)
This textbook examines the extent to which moral values play a role as productive forces for the economy, and explores the effect of ethical and unethical Behavior on the economy. It shows how ethics improves productivity in the economy, and provides specific ethics tools for practical application for students and managers. Stemming from an overall interdisciplinary approach, and combining recent research results from sciences such as economics, business administration, Behavioral economics, philosophy, psychology and sociology, this textbook fills a gap in the literature on ethics in business. The book begins with the foundations of business ethics by defining business ethics, delineating its objectives, and discussing the importance of business ethics for business, the economy and society. Next, it presents the ethical evaluation approaches to enable the reader to evaluate economic Behavior ethically. It then explores 'man in business', and deals with such issues as Behavior, motivation, ethical orientation, and the presence or absence of a sense of justice. Following this is a discussion of the rules of the market and of questions such as: Does the market economy promote ethical Behavior or is there a conflict of goals between ethics and market economy? Do companies have a social responsibility? The book concludes with an analysis of the importance of ethics for productivity in the enterprise and in the economy, and presents ethics tools as the instruments with which management can promote ethical Behavior of their employees. Following a textbook structure, the book first derives knowledge from scientific studies that is relevant for students, and then summarizes the results. It explains ethical assessment approaches, and then gives an ethical assessment of economic Behavior using case studies. It uses roleplaying and games to explain the Behavior of people in relation to ethics.